2010
DOI: 10.1111/j.1365-2966.2010.16307.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the MEGNO technique to the dynamics of Jovian irregular satellites

Abstract: We apply the Mean Exponential Growth Factor of Nearby Orbits (MEGNO) technique to the dynamics of Jovian irregular satellites. The MEGNO indicator is a practical numerical tool to distinguish between quasi‐periodic and chaotic structures in phase space of a given dynamical system. The MEGNO indicator is used to generate a mapping of relevant phase‐space regions occupied by observed Jovian irregular satellites. The construction of MEGNO maps of the Jovian phase‐space region within its Hill‐sphere is addressed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 63 publications
3
88
0
1
Order By: Relevance
“…Later works have shown that at least the totality of the satellites known in 2003 with a precisely determined orbit (30 objects) do not escape over a very long time (Nesvorný et al 2003; see also Yokoyama et al 2003), and averaged elements were found for these satellites that show their organization in families (Nesvorný et al 2003(Nesvorný et al , 2004, an important fact that was confirmed analytically (Beaugé & Nesvorný 2007). Concerning stability studies of the phase space structure of the satellite region, numerical integrations of fictitious satellites (Carruba et al 2002;Yokoyama et al 2003;Nesvorný et al 2003;Hinse et al 2010) confirm the different dynamical portraits obtained between prograde and retrograde regions (Hénon 1969(Hénon , 1970. The study of the overall dynamical structure of the Jovian satellite region with the determination of the various important mean motion resonances for the three-body problem has been done by Hinse et al (2010).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Later works have shown that at least the totality of the satellites known in 2003 with a precisely determined orbit (30 objects) do not escape over a very long time (Nesvorný et al 2003; see also Yokoyama et al 2003), and averaged elements were found for these satellites that show their organization in families (Nesvorný et al 2003(Nesvorný et al , 2004, an important fact that was confirmed analytically (Beaugé & Nesvorný 2007). Concerning stability studies of the phase space structure of the satellite region, numerical integrations of fictitious satellites (Carruba et al 2002;Yokoyama et al 2003;Nesvorný et al 2003;Hinse et al 2010) confirm the different dynamical portraits obtained between prograde and retrograde regions (Hénon 1969(Hénon , 1970. The study of the overall dynamical structure of the Jovian satellite region with the determination of the various important mean motion resonances for the three-body problem has been done by Hinse et al (2010).…”
Section: Introductionmentioning
confidence: 93%
“…Concerning stability studies of the phase space structure of the satellite region, numerical integrations of fictitious satellites (Carruba et al 2002;Yokoyama et al 2003;Nesvorný et al 2003;Hinse et al 2010) confirm the different dynamical portraits obtained between prograde and retrograde regions (Hénon 1969(Hénon , 1970. The study of the overall dynamical structure of the Jovian satellite region with the determination of the various important mean motion resonances for the three-body problem has been done by Hinse et al (2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, first-order variational equations have been widely used to calculate Lyapunov exponents and the Mean Exponential Growth of Nearby Orbits (MEGNO, Cincotta et al 2003) in the astrophysics community (Tancredi et al 2001;Hinse et al 2010). We speculate that higher-order variational equations may be able to improve such chaos indicators.…”
mentioning
confidence: 99%
“…In NIMASTEP, we adopt the same strategy as Goździewski et al (2001) for the numerical computation of the MEGNO. This indicator has been successfully used in some papers, for instance, Breiter et al (2005), Cincotta & Simó (2000), Goździewski et al (2001Goździewski et al ( , 2008 and Hinse et al (2008Hinse et al ( , 2010. For the results concerning the MEGNO implemented into NIMASTEP we refer the reader to Valk et al (2009a) and Compère et al (2012).…”
Section: Megno: Mean Exponential Growth Factor Of Nearby Orbitsmentioning
confidence: 99%